Cyberspace and the Cyberdildo: Dislocations in Cenicienta en Chueca - Jill Robbins (Studies in 20th & 21st Century Literature, 2006)
Cenicienta en Chueca (Cinderella in Chueca) is a collection of short stories by Argentine exile María Felicitas Jaime, published by Spanish gay/lesbian press Odisea in 2003, that represent the neocolonial relations between the Americas, Spain, and the European Union in a globalized age. The stories foreground communication technologies—including type, e-mail, chats, and dialects—in order to highlight the discursive nature of sexuality and to reveal the social, ethnic, racial, nationalistic, economic, gendered tensions underlying linguistic exchange. This article focuses on the neocolonial relations between Spain and Latin America in three stories from this collection—"Chateo" (Chat), "Ejecutivas" (Women Executives), and "Cenicienta en Chueca."
Keywords: Cenicienta en Chueca; Cinderella en Chueca; Argentine Literature; María Felicitas Jaime; gay/lesbian; gay; lesbian; Odisea; neocolonialism; globalized age; communication technology; sexuality; discursive; gender; gender relations; Chateo; Ejecutivas